Simplify :

A. (-2)(-3)

B. (-2)(3)

C. (2)(-3)

D.(2)(3)

Basically we just multiply and put a plus or minus sign.

If there is an even number of negative numbers, the answer is positive. If there is an odd number of negatives, the answer is negative.

A (-2) (-3) = -2 x -3 = 6 ( two negatives even so answer positive)

B (-2) (3) = -2 x 3 = -6 (one negative odd so answer nigative)

C (2) (-3) = 2 x -3 = -6 same as B

D (2)(3) = 2 x 3 = 6 no problem here

any problems or questions, contact me asap

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up